A local portrait of South African counselling psychologists' endorsement of the values and scope of practice of their profession in relation to their career satisfaction - Ngobeni, Nhlori (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
The 2011 revision to the scope of practice of counselling psychology in South Africa has renewed debates about what is it that should distinguish counselling psychology as a distinctive area of practice and research in South Africa. This study reports the findings of a survey of a sample of 228 South African registered counselling psychologists, including the extent to which they endorse the traditional values of their category, the extent to which they endorse the current scope of practice for counselling psychology, and measures of career satisfaction. Findings are that women and white practitioners comprise the large majority of the category. Counselling psychologists strongly endorse most of the traditional values of the category and are generally highly satisfied with their careers. Surprisingly, given these findings, only a large minority indicate that they would choose counselling psychology again knowing what they know now. Most significant, the findings of a multiple regression analysis indicate that endorsement of the scope of practice most strongly predicts career satisfaction scores, followed closely by black racial identification, years of experience, and then endorsement of counselling psychology values. Logistic regression analysis to predict which counselling psychologists would choose counselling psychology again knowing what they know now, revealed that only endorsement of counselling psychology values and endorsement of the scope practice made a significant contribution to predictions. This study provides a snapshot of the current status of South African counselling psychology today and it remains that in the next ten years, there will be significant changes as the category changes across the globe.
Keywords: Counseling psychology -- South Africa; Counseling psychologists -- South Africa; Psychology -- South Africa; Psychologists -- South Africa